Acute lymphoblastic leukemia (ALL) with KMT2A gene rearrangement in infants - characteristic clinical picture based on a case report - Kowalczuk, Maria; Lipińska, Justyna; Lipiński, Łukasz; Lejman, Monika; Zawitkowska, Joanna (Journal of Education, Health and Sport, 2022)
The most common malignancy affecting children is leukemia, which in infants refers to be diagnosed before 1 year of age and is relatively rare, but remains a problem for clinicians due to its aggressive clinical presentation, poor response to current treatments, and molecular biology. Infants with acute leukemia tend to present with aggressive features, including hyperleukocytosis, hepatosplenomegaly, central nervous system (CNS) involvement, and cutaneous infiltration. In infant leukemia, the KMT2A gene rearrangement at chromosome 11q23 is quite common. Infants diagnosed with acute leukemia harboring a 11q23 rearrangement have a particularly poor prognosis when compared to other children with acute leukemia. A 10-month-old girl was admitted in December 2017 to the Department of Pediatric Hematology, Oncology and Transplantology in Lublin with the suspicion of leukemia. One week before hospitalization minor bruises began to appear on the skin, unrelated to an injury. The child was admitted to the hospital, and there a complete blood count showed anemia, hiperleukocytosis and thorombocytopenia. On the admission to the Clinic: the severe general condition of the patient, with features of cardiopulmonary insufficiency were confirmed. Due to the patient's age and the presence of the KMT2A/MLLT3-t(9;11) (p22;q23) gene rearrangement, the infant was stratified as a high-risk group (HRG) and chemotherapy was started in accordance with the therapeutic program. Infant leukemia is one of the most difficult clinical situations encountered in pediatric oncology. Given the infant’s vulnerability and unique genetic rearrangements, there is a need to develop new protocols and therapies for infants.